ANALYSIS OF PRODUCTION EFFICIENCY IN HYBRID CORN SEED FARMING IN RANDUBLATUNG DISTRICT BLORA REGENCY - Kurnia, Septy Alif; Ekowati, Titik; Handayani, Migie (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Efficiency is important to know to see the success of a farming business. Farming activities in producing a product cannot be separated from the use of production factors. Using production factors appropriately and efficiently will provide benefits for farmers, namely maximum productivity. This research aims to analyze the factors that influence hybrid corn seed production, as well as analyzing technical, allocative and economic efficiency. The research location is Randublatung District, Blora Regency, Central Java. The research method used was a case study of seed breeder farmers in Randublatung District using saturated sampling with a total sample of 53 farmers. The analytical method used is quantitative descriptive analysis which includes influence analysis, technical, allocative and economic efficiency analysis using Stochastic Frontier. The results of the research show that there is a simultaneous influence between land variables, seeds, urea fertilizer, phonska fertilizer, pesticides and labor on hybrid corn production results. The variables of land area, seeds and urea fertilizer partially have a significant effect on production results, while the variables of phonska fertilizer, pesticides and labor partially have no effect on production results. The technical efficiency results of hybrid corn farming in Randublatung District are quite technically efficient with an average technical efficiency value of 0.878. The results of the analysis of allocative and economic efficiency show that it is not yet efficient with average values of 0.337 and 0.293 respectively. Opportunities to increase the efficiency of hybrid corn seed farming in Randublatung District include farmers better allocating inputs according to their needs so that input costs are not large, providing more intensive counseling and assistance to farmers regarding hybrid corn seed cultivation techniques, especially in the use of inputs so that they are more proportional in accordance with recommendations from relevant agencies.